Parents' Weekend presentation on bridges by Civil and Environmental Engineering Professor Brian Brenner in Pearson 104. Photo 019 - Loeb, Brian (Tufts Archival Research Center, 2008)
Parents' Weekend presentation on bridges by Civil and Environmental Engineering Professor Brian Brenner in Pearson 104. Brenner's students helped parents build bridge models designed for elementary schools.